Dexmedetomidine Exerted Anti-arrhythmic Effects in Rat With Ischemic Cardiomyopathy via Upregulation of Connexin 43 and Reduction of Fibrosis and Inflammation - Wu, Shu-jie; Lin, Zhong-hao; Lin, Yuan-zheng; Rao, Zhi-heng; Lin, Jia-feng; Wu, Lian-pin; Li, Lei (Frontiers in Physiology, 2020)
Background---Persistent myocardial ischemia occurred in post-myocardial infarction could lead to fatal ventricular arrhythmias like ventricular tachycardia and fibrillation and also has high rate of mortality. Dexmedetomidine (Dex), a highly selective α2-agonist, applied for daily anesthetic practice prevalently, was associated with a decrease in postoperative mortality and decreased incidence of postoperative complications and delirium in patients under cardiac surgery. Present study investigated the effects of dexmedetomidine on arrhythmogenic properties following ischemic cardiomyopathy (ICM) after post-myocardial infarction. Methods and results---48 rats developing ischemic cardiomyopathy after persistent ligation of left anterior descending artery for 4 weeks were divided into 6 groups randomly: Sham (n=8), Sham+BML (n=8), ICM (n=8), ICM+BML (n=8), ICM+Dex (n=8), ICM+Dex+BML (n=8). Treatments were started after the ischemic cardiomyopathy was confirmed (the day after echocardiographic measurement) in rats and continued for 4 weeks (inject intraperitoneally, daily). Dexmedetomidine treatment restrained the production of collagens, cytokines, and other inflammatory mediators in rats with ischemic cardiomyopathy via suppressing NF-κB activation, and increased the distribution of connexin 43 (Cx43) through eliciting phosphorylation of adenosine 5‘-monophosphate-activated protein kinase (AMPK). Additionally, dexmedetomidine reduced the occurrence of ventricular arrhythmia (ventricular premature beat or ventricular tachycardia) and decreased inducibility quotient of ventricular arrhythmias by PES as well as improving cardiac contraction partly. BML-275 dihydrochloride (BML), the AMPK antagonist, weakened the cardio-protective effect of dexmedetomidine, demonstrated as inhibiting the anti-inflammatory and anti-arrhythmic effects of dexmedetomidine. Conclusion---Dexmedetomidine conferred anti-arrhythmia effects in ischemic cardiomyopathy after post-myocardial infarction through regulation of connexin 43 and suppression of fibrosis and inflammation. Eliciting of phosphorylation of adenosine 5’-monophosphate-activated protein kinase and suppressing of NF-κB activation subsequently might contribute to the anti-arrhythmic and anti-inflammatory properties of dexmedetomidine.